Comprehensive Threat Response Model for the Prevention of Website Intrusion - Lee, Yong-joon; Lee, Jeong-min; Kim, Jin-seob; Park, Jae-pyo (International Journal of Engineering and Technology, 2019)
The purpose of this study is to verify the effectiveness of a model capable of comprehensive defense against malicious code attacking websites by using technology to cope with website Intrusion. In this study, we suggest a comprehensive response system model against website intrusions with five security functions, for a comprehensive action against the intrusions occurring through websites. The proposed comprehensive response model against website intrusion attacks is designed to make an overall action against malicious codes through the websites using five response techniques, in terms of the following three stages: prevention, detection, and recovery. The proposed five response techniques include web vulnerability pre-checking, the detection of homepage-spread malicious codes, the detection of zombie PC through malicious code address change, the cyber treatment service, and DDoS (Distributed Denial of Service attack) cyber shelter. An empirical experiment was used for the cases of website intrusion attacks to prove that it was possible to make an efficient action. Experimental results show that 12,191 vulnerabilities have been detected through preliminary checks of web vulnerabilities and 2,932,979 zombie PCs have been blocked. We also detected 9,778,683 PCs infected with malicious code and verified the effectiveness of this proposed model. Â We expect it will be possible to make effective responses against the intrusion attacks using the comprehensive response system model for websites suggested in this study.Â Â